Consciência política e participação dos estudantes de administração no combate à corrupção no Brasil - Farias, Erika Melo (2018)
This paper analyzes the dynamics of political consciousness of undergraduate students in business administration, a federal brazilian public University on the participation in collective actions to fight corruption in Brazil. The discussion is based on th